La iniciativa comunitaria LEADER 11 y el desarrollo rural: el caso de Aragón - Ruiz Budría, Enrique; Frutos Mejías, Luisa María; Climent López, Eugenio (Geographicalia, 2016)
In this paper we review the results of European Union initiative LEADER11 in Aragon (Spain), where 13 areas (53 per cent of the regional territory) has been involved, just finished its in force period (1995-1999). Expenses binded in the approved projects has been 20 per cent higher than forecast ones, private capital contributing 70 per cent. This has been especially invested in production activities, while public capital has been in productive environment ones. Both, private and public investments, have strengthened prior economic specialization in manufacturing and tourist industry of some areas, but they have contributed to diversify agrarian specialized economic structure of most ones.